Secret sauce : how to pack your messages with persuasive punch - Mills, Harry, 1950- (AMACOM, 2017)
This book shows you how to transform unconvincing messages into compelling copy. It comes with a 15-question SAUCE test and a Heat Gauge which allows you to precisely measure the persuasive impact of your messages.